SENYAPAN DAN KILIR LIDAH PADA DEBAT CAWAPRES 2024 - Natasya Aisyiyah Dzikrillah; Anys Melina; Fahrudin Eko Hardiyanto; Etika Widi Utami (Lateralisasi, 2025)
Silence is a mental process in producing speech. It usually occurs when someone is having a conversation and needs additional time to describe what they want to convey in spoken form. This study aims to identify silences that occurred in the 2024 vice presidential debate. In addition to looking for silences, in this study, we also examined the vice presidential candidates' speech errors in the form of slips of the tongue. A slip of the tongue itself can be defined as a phenomenon in speech production where the speaker "slips" the tongue so that the words that come out during communication are not the intended or actual words. The technique or method used in data collection in this study was listening and note-taking. We watched the 2024 vice presidential debate on the Kompas TV YouTube channel and found 20 data points in the form of silences and slips of the tongue.